2009
DOI: 10.4067/s0716-078x2009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Complex bioclimatic and soil gradients shape leaf trait variation in Embothrium coccineum (Proteaceae) among austral forests in Patagonia

Abstract: Patterns of trait variation may be adaptive when vary in relation to an environmental gradient. In particular, leaf traits can affect productivity and competitive ability. We identify patterns of leaf size and shape variation with environmental heterogeneity in one of the most widespread tree species within temperate South America: Embothrium coccineum (Proteaceae). We collected leaf specimens and composite soil samples from 35 populations between 38º and 55º S latitude in Patagonia, covering a wide range of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
3
27
2
1
Order By: Relevance
“…Las variaciones de atributos funcionales a lo largo de gradientes de altitud ha sido abordada por una serie de estudios (Arnold & Mauseth 1999, Cavieres et al 2000, Cabrera 2002, Alberdi & Donoso 2004, Souto et al 2009). Las más estudiadas han sido las variaciones en los conductos xilemáticos (densidad, diámetro y conductividad hidráulica relativa de los vasos) (Mauseth 1999, Davis et al 1999, Arias & Terrazas 2001, Hacke & Sperry 2001, Ladjal et al 2005, en la altura (Cavieres et al 2000, Körner 2003, Falster & Westoby 2005, y en la suculencia de las plantas (Mauseth 1999(Mauseth , 2000(Mauseth , 2006 especialmente en especies que crecen en condiciones limitantes y/o a mayores altitudes (Körner 2003).…”
Section: Discussionunclassified
“…Las variaciones de atributos funcionales a lo largo de gradientes de altitud ha sido abordada por una serie de estudios (Arnold & Mauseth 1999, Cavieres et al 2000, Cabrera 2002, Alberdi & Donoso 2004, Souto et al 2009). Las más estudiadas han sido las variaciones en los conductos xilemáticos (densidad, diámetro y conductividad hidráulica relativa de los vasos) (Mauseth 1999, Davis et al 1999, Arias & Terrazas 2001, Hacke & Sperry 2001, Ladjal et al 2005, en la altura (Cavieres et al 2000, Körner 2003, Falster & Westoby 2005, y en la suculencia de las plantas (Mauseth 1999(Mauseth , 2000(Mauseth , 2006 especialmente en especies que crecen en condiciones limitantes y/o a mayores altitudes (Körner 2003).…”
Section: Discussionunclassified
“…As shown by Marcysiak (), the amount of precipitation during the growing season is positively correlated with leaf length. Furthermore, Souto et al () found that temperatures and precipitation during the growing season are much more important for the leaf formation than the same parameters during winter period. However, at the local scale (Primorsky Krai), we found that the synchronous increase of leaf length, width and area is highly correlated to precipitation seasonality (r 2 = 0.11, r 2 = 0.13 and r 2 = 0.12) and the amount of precipitation during the winter season (r 2 = 0.11, r 2 = 0.11 and r 2 = 0.10), although not as strongly as to the amount of precipitation during the growing season (r 2 = 0.06, r 2 = 0.14 and r 2 = 0.09).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, mean annual temperature and precipitation determine the presence and prominence of leaves dissection (Peppe et al 2011). However, Souto et al (2009) showed that precipitation and temperature during the growing season have a greater influence on leaf parameters than do their annual averages. Precipitation is the most important factor during the growing season, and it is positively correlated with leaf length (Royer and Wilf 2006, Peppe et al 2011, Marcysiak 2013.…”
mentioning
confidence: 99%
“…The adaptation of leaf structure, morphologically or histologically, often reflects clearly the effect of environmental stress and therefore is often used as an index evaluating the impacts of environmental conditions on plants (Dinis et al 2011;Souto et al 2009). The significant interactive effect of ecotype and transpiration regulation (P<0.05) indicated that different ecotypes had varying responses to transpirationaltering measures.…”
Section: Discussionmentioning
confidence: 99%